A mathematical analysis of a hydraulic binary counter for hydraulic exoskeleton actuation. Issue 2 (2018) - Scheidl, Rudolf; Mittlböck, Simon
Low weight and compactness are the main requirements on components for exoskeletons. For drives this means also high efficiency to keep energy storage and power transducing devices small. The digital hydraulic cylinder drive is an excellent candidate to become a superior technology for exoskeleton actuation. It requires several valves to control pressure in its many chambers. Solenoid valves suffer from the high weight and space of the solenoids. In this paper, the hydraulic binary counter in a configuration with only passive elements is studied mathematically, since it can control a digital cylinder with much smaller space and weight than magnetically actuated valves. From qualitative considerations of the system equations supplemented by a numerical study, it is shown that such a counter works properly. But it poses requirements on the control pressure range which are difficult to fulfil for digital cylinder drives with more than five chambers.